Prognostic Implications of Tumor Diameter in Association With Gene Expression Profile for Uveal Melanoma - Walter, Scott D. (JAMA Ophthalmol, 2016)
IMPORTANCE: Uveal melanoma (UM) can be divided into prognostically significant subgroups based on a prospectively validated and widely used 15-gene expression profile (GEP) test. Class 1 UMs have a low risk and class 2 UMs have a high risk for metastasis. OBJECTIVE: To determine whether any clinicopathologic factors provide independent prognostic information that may enhance the accuracy of the GEP classification. DESIGN, SETTING, AND PARTICIPANTS: This retrospective observational study performed at 2 ocular oncology referral centers included 339 patients in a primary cohort and 241 patients in a validation cohort. Both cohorts had a diagnosis of UM arising from the ciliary body and/or choroid. All patients underwent tumor biopsy for GEP prognostic testing. Clinicopathologic variables included patient age and sex, tumor thickness, largest basal tumor diameter (LBD), ciliary body involvement, and pathologic cell type. Patients from the primary cohort were enrolled from November 1, 1998, to March 16, 2012; from the validation cohort, from November 4, 1996, to November 7, 2013. Follow-up for the primary cohort was completed on August 18, 2013; for the validation cohort, December 10, 2013. Data were analyzed from November 12, 2013, to November 25, 2015. MAIN OUTCOME AND MEASURES: Progression-free survival (PFS). The secondary outcome was overall survival. RESULTS: The primary cohort included 339 patients (175 women [51.6%]; mean [SD] age, 61.8 [13.6] years). The most significant prognostic factor was GEP classification (exp[b], 10.33; 95% CI, 4.30–24.84; P < .001). The only other variable that provided independent prognostic information was LBD (exp[b], 1.13; 95% CI, 1.02–1.26; P = .02). Among class 2 UMs, LBD showed a modest but significant association with PFS (exp[b], 1.13; 95% CI, 1.04–1.24; P = .005). The 5-year actuarial metastasis-free survival estimates (SE) were 97% (3%) for class 1 UMs with LBD of less than 12 mm, 90% (4%) for class 1 UMs with LBD of at least 12 mm, 90% (9%) for class 2 UMs with LBD of less than 12 mm, and 30% (7%) for class 2 UMs with LBDs of at least 12 mm. The independent prognostic value of LBD and the 12-mm LBD cutoff were corroborated in the independent validation 241-patient cohort. CONCLUSIONS AND RELEVANCE: Class 2 UMs had better prognosis when the LBD was less than 12 mm at the time of treatment. These findings could have important implications for patient counseling, primary tumor treatment, clinical trial enrollment, metastatic surveillance, and adjuvant therapy.